Mechanism of Interaction of Adsorbent and Adsorbate - M.A. Mamadjonova; D.S. Salihanova; O.S. Karimov (Research Parks Publishing LLC, 2021)
Adsorption refining was carried out in the laboratory to determine the equilibrium time of the